Shy-Drager syndrome a case report with polysomnography - F. S. Aloe; P.E. Marchiori; R.N. Reimão; M. Scaff (Arquivos de Neuro-Psiquiatria)
The authors report a case of Shy-Drager syndrome in a 53 year-old male patient. Autonomic failure was made evident by physical examiration as well as laboratory tests. A sleep recording showed decreased percentage of REM sleep and apneas of the central type. The possible mechanisms for this sleep disorder are discussed.